2019
DOI: 10.1186/s41016-019-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Twist drill craniostomy for traumatic acute subdural hematoma in the elderly: case series and literature review

Abstract: Background: A large craniotomy is usually the first choice for removal of traumatic acute subdural hematoma (TASDH). To date, few studies have reported that TASDH could be successfully treated by twist drill craniostomy (TDC) alone or combined with instillation of urokinase. We aimed to define the TDC for the elderly with TASDH and performed literature review. Case presentation: A total of 7 TASDH patients, who were presented and treated by TDC in this retrospective study between January 2009 and May 2017, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[15,[35][36][37][38][39] Miki et al [15] performed endoscopic surgery under general anesthesia in 26 patients with ASDH over 65 years of age, achieving a mean hematoma reduction rate of 90% and a favorable outcome of 69.2%. Huang et al [17] reported that seven patients over 65 years of age with ASDH achieved more than 70% of hematoma evacuation using twist drill craniotomy under local anesthesia. In patients with ASDH, the delay from injury to surgery is an essential factor influencing a patient's mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,[35][36][37][38][39] Miki et al [15] performed endoscopic surgery under general anesthesia in 26 patients with ASDH over 65 years of age, achieving a mean hematoma reduction rate of 90% and a favorable outcome of 69.2%. Huang et al [17] reported that seven patients over 65 years of age with ASDH achieved more than 70% of hematoma evacuation using twist drill craniotomy under local anesthesia. In patients with ASDH, the delay from injury to surgery is an essential factor influencing a patient's mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, minimally invasive surgery has become an essential topic of discussion, as revealed in a recently published study of minimally invasive surgical techniques such as endoscopic surgery in patients with ASDH at a high risk of complications associated with a large craniotomy. [13][14][15][16][17] In this study, we report an alternative strategy for primary treatment and rescue that involves reducing the mass effect of a subdural hematoma through minimally invasive surgery without general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported positive results of burr hole surgery in patients for whom general anesthesia or craniotomy have a high risk. [ 6 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 14 , 15 ] It was also used in previous reports of burr hole surgery for ASDH, and no complications were reported. [ 1 , 6 ] We also used urokinase, expecting for hematolytic effect. A median of 3 days was required for hematoma excretion after burr hole surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation